THE IMPACT OF ACQUISITION ON FINANCIAL PERFORMANCE OF PT. ABC - Novian Zen; Noer Azam Achsani; Trias Andati (School of Business, IPB University (SB-IPB), 2016)
This study aimed to analyze the financial performance of the subsidiary company (PT ABC) before and after acquired by the holding company (PT XYZ). The examined ratios of the financial performance were profitability and capital structure for the period of 2010-2014. This study utilized the t test tool. In the first and second year after the acquisition, the result shows that with the existence of business synergy, there was a change in financial performance although it was insignificant. Furthermore, in the third year, there was absolutely no change; however, in the fourth year, there was an insignifant change. The implications of this research indicates the motive or objective of the shareholders (K-State-owned Enterprises) in assigning the holding company (XYZ) to restructure the financial performance and improve capital structure of its subsidiary company (PT ABC) by conducting a business synergy has not been reached.Keywords: acquisition, financial performance, improved capital structure, business synergy and financial reports